Field-induced assembly of fibrous network structures in magneto-rheological fluids - Robinson, D (2016)
Self-assembly is a process by which a disordered system becomes an organised, complex structure as a result of a given chemical or physical change. Many experiments have been able to show the effect of an applied field on the self-assembly of superparamagnetic, micrometre scale particles at a low surface coverage. As such, particle positions are able to be monitored in real time from which the chain aggregation process can be analysed in terms of coordination environments. Therefore mathematical and simulation models have become useful in order to describe the interaction between particles and act as a predictive tool for future experimental research. The majority of simulation work regarding electro- and magneto-rheology attaches a permanent, fixed dipole to the particles and measures the response to an applied field. This thesis employs and justifies a model where particles are fully (dipole) polarizable with dipoles induced both by an external field (the direction and magnitude of which may be controlled) and by the presence of other dipole moments (dipole-induced-dipole effects) and consequently the potential contains a many-body character. A `real' particle system is necessarily represented by a dispersion of polarizabilities (magnetizations) which is the motivation for the choice of model. Two models are therefore employed to investigate the effects of the dipole-induced-dipole term in bulk systems containing monodisperse particles and bidisperse particles respectively. Justification of the model allows prediction of more complex systems, namely confined systems as discussed in the final chapter.